Flash flood (Δ) risk and damage assessment in batu, East Java - Dekka Dhirgantara Putra; Bahrul Fikry Sofwany; Hukma Zulfinanda; Iqbal Kamaruddin (Jurnal Teknosains, 2022)
Hydrometeorological disasters are showing an increasing trend in Indonesia. Flash floods are part of a hydrometeorological disaster that has a significant livelihood impact. Flash Flood is triggered by the intensity of extreme rain, several actions of mitigation can be taken by early warning systems, hazard and risk mapping, community preparedness, and climate change adaptation. So, how does future land use have an impact, and how much loss will result from the flash flood disaster in Batu City? The hydrometeorological disaster that occurred in Indonesia was the Batu Flash Flood. The Flash Flood occurred on November 4, 2021. The flash flood has a lot of impact on many locations, including the Bumiaji District and Junrejo District. Based on the disaster history recorded, the flash flood in Batu has only happened once, but the impact was quite big because there are many houses in the midstream of Bulukerto. Based on the losses caused, this can be the basis for efforts to control the spatial pattern of Batu City in the future. The methodology used in this study is risk assessment. While the risk study related to delta (Δ) the study of flash floods risk in spatiotemporal prevention uses the 2030 spatial plan for delta prediction (Δ), which can later predict the consequences of climate change and meteorological disasters from flash floods in Batu. The results of this study are the delta (Δ) of flash flood risk and the damage assessment of the flash flood that occurred in Batu.